Measurement setup consideration and implementation for inductively coupled online impedance extraction - Zhao, Zhenyu (Nanyang Technological University, 2021)
The online impedance serves as a key parameter for evaluating the operating status and health condition of many critical electrical systems. For its non-contact nature and ease of on-site implementation, the inductive coupling approach is a superior method to extract the online impedance of the electrical systems. However, all earlier reported works of this approach have assumed that the online impedance of an electrical system is time-invariant for a specific time interval. Therefore, little work has been explored to extract the time-variant online impedance of any electrical systems, especially those systems with frequent impedance changes. Besides, the effect of the probe-to-probe coupling between the inductive probes used in this approach on the accuracy of the extracted online impedance has not been evaluated, especially when the inductive probes are placed very close to each other due to space constraints in some special circumstances. Moreover, in the harsh industrial environment where significant electrical noise and power surges are present, the existing measurement setup of this approach lacks the necessary signal-to-noise ratio (SNR) and front-end protection to the measurement instruments, and consequently, the application of this approach becomes challenging in such an environment. To overcome the above-mentioned limitations and challenges, this thesis proposes an improved measurement setup of the inductive coupling approach and develops a moving window discrete Fourier transform (DFT) algorithm so that it has the ability to extract not only the time-invariant online impedance but also the time-variant online impedance of electrical systems. In addition, based on a three-port network concept, a comprehensive equivalent circuit model of the proposed measurement setup is described, in which the effect of the probe-to-probe coupling can be taken into account in the model. With the three-port equivalent circuit model, a three-term calibration technique is proposed to deembed the effect of the probe-to-probe coupling with the objective to improve the accuracy of online impedance extraction. Furthermore, by incorporating signal amplification and surge protection modules into the proposed measurement setup, the SNR can be enhanced and the damage to the measurement instruments caused by the power surges can be avoided. With these improvements in the measurement setup of the inductive coupling approach, it opens the door for the application of this approach in many electrical systems, especially those with significant electrical noise and power surges. Based on the proposed measurement setup and the associated theories, the inductive coupling approach has been validated experimentally to show its ability to detect the incipient stator faults online in the inverter-fed induction motor, which shows its capability for online condition monitoring of the electrical system. Besides, this approach has also been demonstrated with the ability to extract the voltage-dependent capacitances of the silicon carbide (SiC) power metal-oxide-semiconductor field-effect transistor (MOSFET). With the extracted voltage-dependent capacitances of the SiC power MOSFET, it facilitates the evaluation of the switching characteristics of the SiC power MOSFET and the associated electromagnetic interference (EMI) noise caused by the switching of the SiC power MOSFET.